Cell Models for Birth Defects Caused by Chloroethyl Nitrosourea-Induced DNA Lesions. Issue 2 (13th March 2021) - Cao, Jiankun; Liu, Zongjian; Wang, Congxiao; Wang, Jie; Pan, Bo; Qie, Shuyan
Abstract : Abstract: Birth defects have been linked to administration of alkylating agents during pregnancy. The anti-tumor efficacy of alkylating agents correlate with their ability to induce DNA lesions, especially interstrand crosslinks (ICLs). Yet the role of DNA damages in birth defects remains to be clarified, owing, in part, to a lack of cell models. Here we generate DNA lesions in NIH/3T3 cells to mimic defects in fetus triggered by 3-Bis(2-chloroethyl)-1-nitrosourea (BCNU, carmustine). CCK-8 assay suggests that BCNU-induced cell death was dose-dependent. Alkaline comet tests and γ-H2AX staining confirm DNA ICLs and other forms of DNA damages caused by BCNUs. The cell cycle analysis shows cells arrest in G2 /M phase until crosslinks repair is complete. Taken together, all these experiments demonstrate we have successfully established normal cell models for birth defects caused by BCNU-mediated DNA damages. The model can not only guide the development of effective and low-toxicity anticancer drugs, but also be of great significance for the study of neonatal malformation triggered by BCNUs.